integral_04

Calculus Level 5

0 ln ( x ) 1 x 2 d x \int _{ 0 }^{ \infty }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx }

The above integral is equal to a π b c \dfrac{-a\pi^b}{c} for positive integers a , b a,b and c c with a a and c c being coprime. Evaluate a + b + c a+b+c .

Note: You are given that ζ ( 2 ) = π 2 6 \zeta(2) = \dfrac{\pi^2}{6} .

inspired by Vishwak Srinivasan


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Hassan Abdulla
May 1, 2018

0 ln ( x ) 1 x 2 d x = 0 1 ln ( x ) 1 x 2 d x + 1 ln ( x ) 1 x 2 d x 1 ln ( x ) 1 x 2 d x = 1 0 ln ( 1 u ) 1 1 u 2 d u u 2 = 0 1 ln ( u ) 1 u 2 d u N o w l e t I = 0 1 ln ( x ) 1 x 2 d x s o 0 ln ( x ) 1 x 2 d x = 2 I 0 < x < 1 1 1 x 2 = k = 0 x 2 k // geometric series I = 0 1 ln ( x ) 1 x 2 d x = 0 1 k = 0 x 2 k ln ( x ) d x = k = 0 0 1 x 2 k ln ( x ) d x I = k = 0 [ x 2 k + 1 2 k + 1 ln ( x ) 0 1 ] 1 2 k + 1 0 1 x 2 k d x = k = 0 1 ( 2 k + 1 ) 2 // integration by part I is only the odd squares so I = [ k = 1 1 k 2 k = 1 1 ( 2 k ) 2 ] = [ k = 1 1 k 2 1 4 k = 1 1 k 2 ] I = [ π 2 6 1 4 π 2 6 ] = π 2 8 0 ln ( x ) 1 x 2 d x = 2 π 2 8 = π 2 4 a + b + c = 7 \int _{ 0 }^{ \infty }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } =\int _{ 0 }^{ 1 }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } +\int _{ 1 }^{ \infty }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } \\ \int _{ 1 }^{ \infty }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } =\int _{ 1 }^{ 0 }{ \frac { \ln { ( } \frac { 1 }{ u } ) }{ 1-\frac { 1 }{ u^{ 2 } } } \frac { -du }{ u^{ 2 } } } =\int _{ 0 }^{ 1 }{ \frac { \ln { ( } u) }{ 1-u^{ 2 } } du } \\ Now\quad let\quad I=\int _{ 0 }^{ 1 }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } \\ so\quad \int _{ 0 }^{ \infty }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } =2I\\0<x<1\Rightarrow \frac { 1 }{ 1-x^{ 2 } } = \sum _{ k=0 }^{ \infty }{ { x }^{ 2k } } \color{#3D99F6} \text{ // geometric series} \\ I=\int _{ 0 }^{ 1 } \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx=\int _{ 0 }^{ 1 } \sum _{ k=0 }^{ \infty }{ { x }^{ 2k }\cdot \ln { ( } x) } dx=\sum _{ k=0 }^{ \infty }{ { \int _{ 0 }^{ 1 } x }^{ 2k }\cdot \ln { ( } x) } dx \\ I=\sum _{ k=0 }^{ \infty }{ { \left[ \frac { { x }^{ 2k+1 } }{ 2k+1 } \ln { ( } x)|_{ 0 }^{ 1 } \right] -\frac { 1 }{ 2k+1 } \int _{ 0 }^{ 1 }{ { x }^{ 2k }dx } } } =-\sum _{ k=0 }^{ \infty }{ \frac { 1 }{ { \left( 2k+1 \right) }^{ 2 } } } \color{#3D99F6} \text{ // integration by part} \\ \color{#D61F06} I \text{ is only the odd squares} \\ \text{so }I=-\left[ \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { k }^{ 2 } } } -\sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { \left( 2k \right) }^{ 2 } } } \right] =-\left[ \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { k }^{ 2 } } } -\frac { 1 }{ 4 } \sum _{ k=1 }^{ \infty }{ \frac { 1 }{ { k }^{ 2 } } } \right] \\ I=-\left[ \frac { { \pi }^{ 2 } }{ 6 } -\frac { 1 }{ 4 } \cdot \frac { { \pi }^{ 2 } }{ 6 } \right] =-\frac { { \pi }^{ 2 } }{ 8 }\\\int _{ 0 }^{ \infty }{ \frac { \ln { ( } x) }{ 1-x^{ 2 } } dx } =2\cdot -\frac { { \pi }^{ 2 } }{ 8 } =-\frac { { \pi }^{ 2 } }{ 4 } \\ a+b+c=7

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...